2022
DOI: 10.3389/fenvs.2022.996515
|View full text |Cite
|
Sign up to set email alerts
|

The role of distinct electricity sources on pollution abatement: Evidence from a wide global panel

Abstract: In this study, we examine the contribution of nuclear, fossil (coal, oil, and gas), and renewable (hydro, solar, wind, biofuel) electricity sources to pollution in the globalization era, as measured by total greenhouse gases (GHG) produced by electricity per capita. We conduct an empirical investigation in a global panel of 163 countries which assesses both the concurrent and individual effects of alternative energy sources. Additionally, we implement a second model to assess the roles of various electricity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 116 publications
0
8
0
Order By: Relevance
“…However, greenhouse gas emissions from one country may contribute to pollution and global warming and negatively impact economic growth in other nations [107]. The study confirmed that fossil fuel is a major source of greenhouse gas emissions and a driver of carbon intensity [58,78]. Most authors concluded that promoting clean and alternative energy sources as an alternative to fossil fuels reduces carbon emissions [80,85,89].…”
Section: Impact Of Greenhouse Gas Emissions On Climatementioning
confidence: 76%
See 3 more Smart Citations
“…However, greenhouse gas emissions from one country may contribute to pollution and global warming and negatively impact economic growth in other nations [107]. The study confirmed that fossil fuel is a major source of greenhouse gas emissions and a driver of carbon intensity [58,78]. Most authors concluded that promoting clean and alternative energy sources as an alternative to fossil fuels reduces carbon emissions [80,85,89].…”
Section: Impact Of Greenhouse Gas Emissions On Climatementioning
confidence: 76%
“…Economic growth necessitates a greater need for energy primarily from fossil fuels, which impacts greenhouse gas (GHG) emissions [80]-a recent study claimed that emissions depend on the kind of energy sources used and concluded that using renewable energy reduced emissions while using nonrenewable energy for electricity generation increased emissions. Although past studies on the effects of low-carbon energy on environmental quality have been conflicting, the use of fossil fuel production of electricity has been proven to have a detrimental effect on the environment [78,94,95]. With the tremendous increase in [80].…”
Section: Data Chartingmentioning
confidence: 99%
See 2 more Smart Citations
“…This methodology differs from the cointegration approach proposed by Johansen (1988) and Engle and Granger (1991), as discussed by Nkoro and Uko (2016) or Philips (2018). Furthermore, ARDL models show higher efficiency when describing the short-versus long-run relationships between variables (Horobet et al, 2022).…”
Section: Data and Research Methodologymentioning
confidence: 92%